Filmowe inspiracje w utworach muzyki popularnej = Cinematic inspirations in popular music - Prusinowski, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Over the course of decades rock and pop artists have referred to cinema in various ways. It`s not only about music videos, which are, in fact, film illustrations of music. References to famous actors and plots of specific films, samples of dialogue and other sound bites from motion pictures, and finally the cases where a song becomes a musical equivalent of a cinematic spectacle - all these references are present in popular music, in both its textual and sonic aspects.
Keywords: film; music; pop; rock; muzyka